PHYSICAL FITNESS OF FREESTYLE WRESTLERS - Abdullaev Zokhidjan Zokirjanovich (PEDAGOGS, 2024)
Annotation: Physical fitness of freestyle wrestlers sports it is considered one of the important components of its training and is a process aimed at developing physical qualities - strength, endurance, flexibility, agility and speed.